(3cTa GdcQhH hOaY GdMQhHs - (3GdMGaX Hf YKeGfs
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd ESfGffG ehVMkG ddHjGf QNUgG ddEfSGf HGdeNGQL hGdJHjGf haVdfG HGdabg Ydi SGFQ GdCee s
(3BNQgG (B:s
(3hGdMeO ddg ChdkG hBNQkG Ydi JeGeg heUdjkG Ydi fHjg hQSdg hNGJeg eMeO hBdg hUMHg hSde JSdjekG cKjQkG OGFekG Edi jhe GdOjf hSdGe Ydi GdeQSdjf hGdMeO ddg QH GdYGdejf JeJ GdQSGdI HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg Mfai Mdje (B48) s
Keywords: (3Gdabg GdMfajs